Polyorquidism: case report comparing ultrasonography and magnetic resonance imaging - Santos,Lucas Ribeiro dos (2020)
Abstract Introduction: polyorchidism is an unusual pathology, about 200 cases in the world literature. Case report: we reported a case of polyorchidism in a 16-year-old male patient diagnosed by ultrasound and confirmed by magnetic resonance imaging. Discussion: most of the cases presented, there is a supernumerary testis, but there are reports on more than three, up to five testicles with supranumerical gonads on both sides of the scrotum. The diagnosis is usually performed in late puberty, incidentally, with a painless scrotal mass or at the emergency room, presenting a testicular torsion of the whole hemiscrotum or supernumerary testisalone, and the differential diagnosis should be made with epididymal cyst and spermatocele, besides other extra-testicular masses (hydroceles, varicoceles, lipomas, tumors.) and para-testicular masses (hernias, scrotal calculi). After the initial clinical evaluation, ultrasound is the first line subsidiary exam. Magnetic Resonance Imaging is very helpful, just in case the ultrasound diagnosis is uncertain. The supernumerary testishave the same Magnetic Resonance Imaging characteristics as the normal testes (intermediate signal intensity on T1- weighted images and high signal intensity on T2-weighted images).